Studying a new anti-polarization method in the process of ultrafiltration of skimmed milk - Deynichenko, Gregoriy; Guzenko, Vasyl; Udovenko, Oleg; Omelchenko, Aleksandr; Melnik, Olga (Eastern-European Journal of Enterprise Technologies, 2016)
The paper presents an experimental research and new methods of processing the findings on the ultrafiltration concentration of skimmed raw milk with the use of a new method to prevent a polarization layer on the membrane. The paper reveals the research findings on the bubbling method effect on a polarization layer in the membrane processing of skimmed milk and on the performance of ultrafiltration membranes. The devised mathematical models are based on the regression equations of the factorial experiment on the selection of technological parameters of the UF-concentration of skimmed milk with the use of the feedstock bubbling over the membrane surface. We have determined the rational working parameters of the process; these working parameters are as follows: the working pressure is 0.4–0.5 MPa, the skimmed milk temperature – 40–50 °C, the skimmed milk bubbling frequency – 0.10–0.15 min-1, and the bubbling pressure – 0.56–0.58 MPa.